Functional properties of yardlong bean (Vigna sesquipedalis Fruw.) protein concentrate - Pascasio, Ma. Kara Isabelle Oronos (UP College of Home Economics, 2011)
ABSTRACT Protein from yardlong bean (Vigna sesquipedalis Fruw.) was extracted using alkaline extraction and isoelectric precipitation. Four extraction procedures were conducted with different pH-incubation time combinations. The yardlong bean protein extraction parameters of pH 10.5 and 60 minutes incubation time which produced the highest yield (45.4%) with a crude protein content of 80.6% was chosen as the most suitable extraction procedure for yardlong bean. Functional properties of the yardlong bean protein was compared with yardlong bean flour and a commercially available soybean protein concentrate. Emulsion capacity , whippability, foam stability, bulk density and water and oil absorption of the yardlong bean extract compared favorably with soybean concentrate. Least gelation concentration of yardlong bean protein concentrate was 18% compared to soybean protein concentrate's 12%. Thus, yardlong bean protein concentrate, with its good functionality can be a good potential ingredient in food products.